PROFESIONAL GURU DALAM MENGHADAPI TANTANGAN PERKEMBANGAN TEKNOLOGI PENDIDIKAN - Muhammad Aspi; Syahrani Syahrani (CV. ADIBA AISHA AMIRA, 2022)
Professional teachers are the determining factor in the quality education process. Teachers in the current era of information and communication technology are not just teaching (transfer of knowledge) but must be learning managers, because education is a gateway to a better life by fighting for the smallest things to the biggest things that would normally be passed by every student. man. Education is required to be more advanced and easily accessible to all people. One of them, the creation of the